Fluid flow and heat transfer characteristics in microchannels - Ang, Gabriel Pau Hwee (2008)
Over the past decade, microscale flow characteristics have been known to deviate from conventional behaviour, owing to two main effects: the electric double layer (EDL) near the solid-liquid interface, and the viscous dissipation effect. In this study, both effects on pressure-driven liquid flow in a microcapillary are studied numerically and experimentally. From past reviews, it was found that viscous heating results in higher flow rate and lower friction, while EDL effect causes reduced flow and higher friction; somewhat contrary to the first?s. This analysis therefore works to study the interaction between these two effects. The results conclude that effects of EDL and viscous dissipation both affect microscale flow characteristics in different ways. The two effects are always present and contributing to the flow characteristics. However, under certain circumstances, one effect may be more significant than the other, leading the flow characteristics towards that phenomenon. Hence, the significance of each effect depends on the physical flow conditions of the fluid.